2018
DOI: 10.1007/978-3-319-93372-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Tipping Points for Norm Change in Human Cultures

Abstract: Humans interact with each other on a daily basis by developing and maintaining various social norms and it is critical to form a deeper understanding of how such norms develop, how they change, and how fast they change. In this work, we develop an evolutionary game-theoretic model based on research in cultural psychology that shows that humans in various cultures differ in their tendencies to conform with those around them. Using this model, we analyze the evolutionary relationships between the tendency to con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
(6 reference statements)
3
25
0
Order By: Relevance
“…In some respects, the latter effect is complementary to a result obtained from models described by De et al (2018) who found that cultural differences in susceptibility to others' influence-which they modeled in an operationally different way-predicted a tendency for populations to reach a "tipping point" at which large numbers of people adopt a new norm in a short period of time. Our models differ from those of De et al (2018) in the operational details and therefore offer a useful complementarity. Not only might more highly influenceable populations be more prone to tipping points, they may also be more prone to the acquisition of new normative beliefs.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…In some respects, the latter effect is complementary to a result obtained from models described by De et al (2018) who found that cultural differences in susceptibility to others' influence-which they modeled in an operationally different way-predicted a tendency for populations to reach a "tipping point" at which large numbers of people adopt a new norm in a short period of time. Our models differ from those of De et al (2018) in the operational details and therefore offer a useful complementarity. Not only might more highly influenceable populations be more prone to tipping points, they may also be more prone to the acquisition of new normative beliefs.…”
Section: Discussionsupporting
confidence: 55%
“…Some recent computational modeling projects have produced results predicting cross-cultural variability in the adoption of new cultural norms (De et al, 2018). This work, which is summarized in the next section, is relevant to our own models, which focus on cultural differences in individuals' susceptibility to social influence and on cultural differences in the social networks through which this influence occurs.…”
Section: Diffusion and Spread Of New Beliefsmentioning
confidence: 99%
See 3 more Smart Citations